A Constructive Classification of Graphs - M. A. Iordanskii (Моделирование и анализ информационных систем)
The classes of graphs closed regarding the set-theoretical operations of union and intersection are considered. Some constructive descriptions of the closed graph classes are set by the element and operational generating basses. Such bases have been constructed for many classes of graphs. The backward problems (when the generating bases are given and it is necessary to define the characteristic properties of corresponding graphs) are solved in the paper. Subsets of element and operational bases of the closed class of all graphs are considered as generating bases.